Quick determination of crystal size distributions of rocks by means of a color scanner - Tarquini, Simone (Image analysis and stereology, 2003)
An acquisition and analysis method based on a commercial, low-cost, high-resolution film scanner is presented. It allows to collect data from standard rock thin sections with a resolution up to 9.4 `m per pixel. Common and general purpose facilities (scanner + PC + image analysis software) may thus be transformed in an appropriate tool for quantitative textural analysis of rocks. The procedure implies the acquisition of four images with crossed polarizers and one parallel light image. Crystal boundaries are extracted fromfields in crossed polarizers, while markers for mineral recognition are obtained thresholding the parallel light image. The method is tested for freshrocks with simple mineralogy (harzburgites and marbles) with no more thanthree phases, all exhibiting well distinct optical properties. Image processing is performed developing procedures with VISILOG 5.2 package. 2-D size data from binary images are converted to 3-D size data applying stereological corrections. 3-D data are reported in bi-logarithmic diagrams, plotting the crystal number density versus characteristic lengths. The harzburgite samples show a scale invariance of size distributions of olivine while mosaic equant marbles exhibit a different size distribution pattern, without scale invariance and a relative maximum.
Keywords: Crystallization; Delec, velikost; Kristalizacija; Particle Size; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; karakterizacija; kristali; porazdelitev velikosti delcev; metode